2005
DOI: 10.1126/science.1115462
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Activation Mediates Inhibition of Axon Regeneration by Myelin and Chondroitin Sulfate Proteoglycans

Abstract: Inhibitory molecules associated with myelin and the glial scar limit axon regeneration in the adult central nervous system (CNS), but the underlying signaling mechanisms of regeneration inhibition are not fully understood. Here, we show that suppressing the kinase function of the epidermal growth factor receptor (EGFR) blocks the activities of both myelin inhibitors and chondroitin sulfate proteoglycans in inhibiting neurite outgrowth. In addition, regeneration inhibitors trigger the phosphorylation of EGFR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
320
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(335 citation statements)
references
References 29 publications
14
320
0
1
Order By: Relevance
“…Both in vitro and in vivo results indicate that PKC is one of the signaling mediators of myelin inhibition. Another study also by He and colleagues concluded that EGFR mediates myelin inhibition (Koprivica et al, 2005). They showed that myelin inhibitors trigger EGFR phosphorylation and in vivo administration of EGFR inhibitors stimulate optic nerve regeneration.…”
Section: Intracellular Signalingmentioning
confidence: 93%
See 1 more Smart Citation
“…Both in vitro and in vivo results indicate that PKC is one of the signaling mediators of myelin inhibition. Another study also by He and colleagues concluded that EGFR mediates myelin inhibition (Koprivica et al, 2005). They showed that myelin inhibitors trigger EGFR phosphorylation and in vivo administration of EGFR inhibitors stimulate optic nerve regeneration.…”
Section: Intracellular Signalingmentioning
confidence: 93%
“…For instance, Rho/ROCK, PKC and EGFR appear to be common mediators of neurite inhibition by both the prototypical myelin inhibitors and the CSPGs (Lehmann et al, 1999;Monnier et al, 2003;Sivasankaran et al, 2004;Koprivica et al, 2005). These observations indicate that such common downstream effectors may offer certain advantages as therapeutic targets.…”
Section: Intracellular Signalingmentioning
confidence: 96%
“…MAG inhibits neurite outgrowth from the postnatal CGNs, and this effect is mediated by several factors, including RhoA, conventional PKC, and the EGF receptor. 6,9 These findings prompted us to examine if the effect of MAG-Fc on neurite outgrowth is also dependent on Rap1 activity. We generated TAT-Rap1A DN and TAT-Rap1A DA -DN and DA forms of Rap1A fused with the N-terminal 11-amino-acid protein transduction domain of the human immunodeficiency virus protein TAT 19 -to enable the protein to gain entry into the cell.…”
Section: Mc192+mag-fcmentioning
confidence: 99%
“…7,8 In addition, phosphorylation of the epidermal growth factor (EGF) receptor is triggered by these myelin-derived inhibitors and is necessary for the inhibitory effect. 9 These multiple signals are responsible for the effects of the myelin-derived inhibitors at least in vitro.In addition to the role of MAG in axon regeneration, experiments with MAG-deficient mice implicate this protein in regulating axonal caliber and the levels of neurofilament spacing in mature myelinated fibers. 10 MAG is suggested to modulate the maturation and viability of myelinated axons.…”
mentioning
confidence: 99%
See 1 more Smart Citation